Replication and innate immune responses of two chikungunya virus genotypes in human monocyte-derived macrophages. (12th April 2023) - Lau, Joanne Zhi Han; Chua, Chong Long; Chan, Yoke Fun; Nadarajan, Veera Sekaran; Lee, Christina Lai Ling; Sam, I-Ching
Abstract : Chikungunya virus (CHIKV) is a re-emerging mosquito-borne virus, which causes epidemics of fever, joint pain and rash. There are three genotypes: West African, East/Central/South/Africa (ECSA) and Asian, with the latter two predominant globally. Genotype-specific differences in clinical presentations, virulence and immunopathology have been described. Macrophages are key cells in immune responses against CHIKV. Circulating blood monocytes enter tissue to differentiate into monocyte-derived macrophages (MDMs) in response to CHIKV infection at key replication sites such as lymphoid organs and joints. This study analyses differences in replication and induced immune mediators following infection of MDMs with Asian and ECSA CHIKV genotypes. Primary human MDMs were derived from residual blood donations. Replication of Asian (MY/06/37348) or ECSA (MY/08/065) genotype strains of CHIKV in MDMs was measured by plaque assay. Nineteen immune mediators were measured in infected cell supernatants using multiplexed immunoassay or ELISA. MY/08/065 showed significantly higher viral replication at 24 h post-infection (h p.i.) but induced significantly lower expression of proinflammatory cytokines (CCL-2, CCL-3, CCL-4, RANTES and CXCL-10) and the anti-inflammatory IL-1Ra compared to MY/06/37348. No differences were seen at later time points up to 72 h p.i. During early infection, MY/08/065 induced lower proinflammatory immune responses in MDMs. In vivo, this may lead to poorer initial control of viral infection, facilitating CHIKV replication and dissemination to other sites such as joints. This may explain the consistent past findings that the ECSA genotype is associated with greater viremia and severity of symptoms than the Asian genotype. Knowledge of CHIKV genotype-specific immunopathogenic mechanisms in human MDMs is important in understanding of clinical epidemiology, biomarkers and therapeutics in areas with co-circulation of different genotypes.